Pengaruh Model Pembelajaran Meaningful Instructional Design terhadap Hasil Belajar Sejarah Siswa Kelas XI di SMA Negeri Noman - Silfi; Agus Susilo; Supriyanto (Attractive : Innovative Education Journal, 2024)
The aim of the research is to determine the effect of the meaningful instructional design learning model on the history learning outcomes of class XI students at SMA Negeri Noman. The research design is in the form of True Experimental Design, pre-test post-test control group design category. The research was conducted at Noman State High School with a population of class XI students. Sampling was carried out with saturated samples so that the samples taken were students from class XI.IPS.1 as the experimental class and class XI.IPS.2 as the control class. Telnol data collection was carried out using a test technique consisting of 30 questions. The collected data was then analyzed using the t-test. Based on the results of the research and discussion, it can be concluded that there is an influence of the use of the Meaningful Instructional Design learning model on the history learning outcomes of class X students at SMA Negeri Noman. This can be seen from the average pretest and posttest scores for the experimental class, which are 62.31 and 85.72. Meanwhile, the average pre-test and post-test scores for the control class were 61.59 and 71.24. So there is a difference in learning outcomes for the experimental class of 24.13 while for the control class it is 9.65. This result is strengthened by calculating the "t" test (hypothesis test) where tcount (7,600) > ttable (2,000) for a significance level of 5% with dk = 60, so that Ho is rejected and Ha is accepted